Formation of Benzodiazepines and Pyrazinylquinoxalines from Aromatic and Heteroaromatic Ketones via Deoximation - Song, J.H.; Bae, S.M; Lee, E.J.; Cho, J.H; Jung, D.I. (Asian Journal of Chemistry, 2020)
The report stated that the treatment of o-phenylenediamine with acetone dicarboxylic acid, acetone and acetophenone afforded 2,4,4-trimethyl-3H-5-hydro-1,5-benzodiazepine. However, direct reactions of o-phenylenediamine with oximes (acetone oxime, acetophenone oxime, and benzophenone oxime) as ketone equivalents did not occur. In the course of present investigations, it is found that dichloroamine-T can be an efficient reagent for the conversion of oximes into the corresponding carbonyl compounds. As a part of a research program related to the synthetic study of pharmacologically interesting benzodiazepine compounds, herein the synthesis of 1H-1,5-benzodiazepine derivatives from heteroaromatic ketones and acetone equivalents obtained using dichloroamine-T. On the other hand, when diamine (1,2-phenylene diamine or 1,2-naphthalene diamine) with heterocyclic ketone (acetyl pyridine or acetyl pyrazines) in the presenece of conc. HCl and SiO2 was refluxed, quinoxaline derivatives as yellow crystalline solids were isolated in high yields.